Short, Finite And One-Sided Bridges In Logoori - Sarvasy, Hannah (My University, 2019)
The Luyia Bantu language Logoori shows a genre-based split in bridging construction distribution. Examination of a small corpus of Logoori texts of various genres told by diverse speakers shows that recapitulative linkage is limited to the genre in which actions are most central: procedural texts. In descriptive texts, where concepts rather than actions are topical, recapitulation occurs in the vessel of NPs, not verbs. Both types of recapitulation are largely absent from narratives. In Logoori recapitulative linkage, the predicate in the bridging clause uniformly takes the Immediate Perfect inflection, meaning ``X having just Ved''. The semantics of this inflection entail that bridging constructions cement a tight sequential relationship between the action described in the reference clause and the clause after the bridging clause. But even within the procedural text genre, recapitulative linkage is unevenly distributed and is apparently replaceable: one speaker uses the Immediate Perfect within a procedural text to effect the same sequential relationship as recapitulative linkage, but without lexical repetition. The intra-genre uneven distribution of bridging constructions, and their absence from narratives, point to their non-essentiality to Logoori discourse coherence.
Keywords: Logoori; Luyia Bantu language; finite